A disaggregated stochastic life-loss model for extreme hydraulic events. Issue 3 (6th August 2019) - Coombs, Rhys
Abstract : The risk factors affecting sheltering populations (i.e. those taking refuge in buildings) are different from those affecting exposed populations (i.e. those on the road). Until now, there have been few stochastic models that account for these differences in risk and historically only lumped stochastic models were applied. This paper presents an alternative and a new life-loss model which allows sheltering and exposed populations to be disaggregated, and for sheltering populations to have a risk profile coupled with anticipated building damage. The new methodology was developed to allow point application for use in two-dimensional hydraulic models.